Penginjilan Strategis melalui Mobile Clinic - Karnius Daniel Fau; Budi Kelana (PT. Penerbit Tiga Mutiara, 2024)
Jesus Christ has finished carrying out the task of saving on the hill of Golgotha. Jesus rose on the third day and was still with His disciples for some time. This togetherness consists of repeating and re-consolidating things related to the salvation that He has provided during his ministry. At the same time, Jesus also gave a command recorded by the writers of Matthew and Mark. The commandment told His disciples to go preach the Gospel to all nations and creatures. Now it was the disciples' job to go ahead and carry out the command. Jesus provided a service concept in the form of an evangelism strategy that could be accepted by the local community. This journal writing is focused on contextual evangelism through the health sector and counseling. This concept needs to be worked out with the wisdom of heaven through the guidance of the Holy Spirit. Seeing the diverse geography, contextual services through Health use a mobile clinic system. The writing of this journal will discuss it in more depth so that it can be understood by every reader and can be applied in every place where evangelism is carried out.